Apixaban for the Treatment of Chronic Disseminated Intravascular Coagulation: A Report of Two Cases - Janjetovic, Snjezana; Holstein, Katharina; Dicke, Christina; Bokemeyer, Carsten; Langer, Florian (Hämostaseologie, 2019)
Characteristic features of disseminated intravascular coagulation (DIC) are the opposing risks of bleeding (due to consumptive coagulopathy and hyperfibrinolysis) and organ failure (due to widespread microvascular thromboses). The purpose of anticoagulation in DIC is to attenuate excessive thrombin generation and fibrin deposition. While heparins have been shown to be beneficial in this context, the safety and efficacy of direct oral anticoagulants have not yet been sufficiently addressed. Here, we report two patients in whom chronic DIC was stabilized upon administration of apixaban: an elderly male with aortic dissection presenting with significant mucocutaneous bleeding and a younger female with Klippel–Trénaunay–Weber syndrome presenting with multiple superficial vein thromboses (SVTs). In addition to an improvement in DIC parameters, both patients benefited clinically with resolution of bleeding symptoms and prevention of further SVTs, respectively. Oral apixaban thus showed promising safety and efficacy in the management of DIC caused by vascular abnormalities; still further investigations are needed to support these findings.
Keywords: disseminated intravascular coagulation; fibrinolysis; apixaban